A clinico etiological study of balanoposthitisin male patients attending the sexual transmitted diseases outpatient department - Deepa, K.; Chitra, C. L.; Manipriya, R. (International Journal of Research in Dermatology, 2019)
Background: The term balanoposthitis refers to inflammation of the glans and the prepuce. It is a widespread condition in male patients attending the genitor-urinary clinic. It may be acute or chronic, occurring most commonly in the uncircumcised men. The aim of the study was to study the incidence of balanoposthitis in all male, to identify the etiological agents by microbiological investigations and the risk factors and the complications associated with balanoposthitis. Methods: Study group consists of 100 male patients presenting with the complaints of pain, pruritus, fissuring of the prepuce and subpreputial discharge attending the STD department were chosen. The detailed history was taken, and clinical examination was done. The subpreputial discharge was collected, and wet mounts, cultures, and subcultures were done. Results: All the patients in the study group with balanoposthitis were uncircumcised. 55% of the patients had some associated systemic disease. Out of the 55 patients, diabetes was present in 45 patients. Of the 51 patients of diabetics, 77.77% were in the recently diagnosed group within the past 5 years. Phimosis and preputial adhesions were the most common complications. The Sensitivity of the KOH wet mount in detecting yeast cells was around 93%. Candida albicans was grown by 56%. In our study, S. aureus (24%) was the most common bacterium isolated. Conclusions: The most common systemic association and the predisposing factor was diabetes mellitus. The infective etiological agents were associated with the majority of balanoposthitis. The most common complication associated with balanoposthitis was phimosis.